Study on Special Shaped Polyester Fibers and Development of Products. Issue 3 (May 2021) - Ge, Yeqian; Deyan, Qin; Hongfang, Wang; Jianhong, Tu; Xuefei, Wang; Bojun, Xi
Non-circular profiled fibers are generally synthetic fibers that have a modified cross-section shape, which are created to mimic natural fibers or to obtain special properties. The shape of the cross-section has great influence on the properties of profiled polyester (PET) fibers and their fabrics. The structure and properties of fat-shaped and hexagonal-shaped profiled PET fibers and ordinary PET fibers, as well as the properties of their knit fabrics were characterized. Experimental results showed that air permeability, heat retention, and wrinkle resilience of profiled PET fabrics were better than that of circular a cross-section PET fiber fabric, while the circular cross-section PET fabric was softer than the profiled PET fiber fabrics.